(untitled) (Iraqi Journal of Civil Engineering, 2023)
This main aim of this study is evaluate wide range of fresh and hardened properties of sustainable self-compacting concrete containing various types of Cement Replacement Materials with optimum contents of Polyethylene Terephthalate PET waste plastic as fibers and fine aggregate replacement. This is to evaluate effect of the two forms of PET and to determine the best CRMs could be used with sustainable SCC. such as limestone, glass powder and fly ash with high replacement rate of 70% by weight of cement were used while fourth one (kaolin) was used with replacement rate of 20%. PET fibers were added to SCC with an aspect ratio of 24.4 and 0.7% volume fraction whereas fine aggregate partially replaced by 4% of waste plastic. Four reference mixtures contained FA, LP, GP and KA only, same four mixtures contained 0.7% PET fibers by volume, and the other same four mixtures contained 4% PET fine aggregate by volume. The obtained results all tested fresh properties, which include slump flow, T500, L-Box and segregation resistance were within the limits of the specification reported in EFNERC guidelines. Further, the forms PET have an adverse effect fresh properties of SCC. As for hardened properties (compressive strength, splitting tensile strength, flexural strength and impact strength). Further, this produced type of SCC showed an range of compressive strength (15.2-31.64 MPa) at 28 days. It can be from the current study the best CRMs to be used in SCC containing PET wastes was FA in terms of most tested properties.